Pulmonary Inflammatory Myofibroblastic Tumor: A Case Report - Lotte Bruyninckx; Paul De Leyn; Dirk Van Raemdonck; Yanina Jansen; Katrien Coppens; Francois Vermeulen; Birgit Weynand; Christopher Gieraerts; Herbert Decaluwé (Georg Thieme Verlag KG, 2024)
An inflammatory myofibroblastic tumor (IMT) is a rare mesenchymal tumor that occurs predominantly in children and young adults. Etiology remains unclear. But based on the frequent detection of chromosomic alterations, especially near the anaplastic lymphoma kinase (ALK) gene, IMT is now considered to be a true neoplasm. In addition, the possible aggressive behavior, and the ability to metastasize suggest at least an intermediate malignant potential. Surgery remains the treatment of choice, but the use of chemotherapy, nonsteroidal anti-inflammatory drugs, immunotherapy, and targeted therapy are reported. We describe a case of a pulmonary IMT in a 6-year-old boy with an incidental finding of a lesion in the right upper lobe. A video-assisted thoracoscopic right upper lobectomy with lymph node resection was performed. Microscopic examination confirmed the diagnosis of IMT with the nodule showing spindle cells in a background of plasma cells. ALK immunohistochemical expression was negative.